Pengaruh Persepsi Pelaku Ukm Tentang Akuntansi Dan Pengetahuan Akuntansi Terhadap Penggunaan Informasi Akuntansi Pada UKM Di Kabupaten Tabanan - Merta Dewi, Ni Putu Sukmawati; Samtika Putra, I Putu Deddy (Hita Akuntansi dan Keuangan, 2024)
The purpose of this research is to ascertain how the beliefs held by UKM actors regarding accounting and accounting knowledge influence the utilisation of accounting data by small and medium-sized enterprises (SMEs) in Tabanan Regency. There were 10,365 UKM in Tabanan Regency included in this study. This study used multiple linear regression analysis on a sample size of 99 UKM actors selected via proportional stratified random sampling. This study’s findings suggest that SME accounting perceptions influence SME accounting information users in a positive and statistically significant way. Knowledge of accounting has a significant and positive effect on how SMEs utilise accounting data. In order to increase the use of accounting information for SMEs at a given business scale, the research shows that all SMEs need to increase the perception of SMEs about accounting and accounting knowledge. This can be done by regularly reading books or watching YouTube videos about accounting, attending seminars and workshops. concerning accounting will greatly aid in elaborating SME understanding of accounting.